ANALISIS KONDISI AKTUAL PENCEMARAN MERKURI BERDASARKAN PETA KERENTANAN PENCEMARAN AIR PERMUKAAN PADA PENAMBANGAN EMAS RAKYAT DESA PANCURENDANG, KECAMATAN AJIBARANG, BANYUMAS - Eni Muryani; Dian Hudawan Santoso; Dayu Aviana Rahmah (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2020)
ABSTRACTThe mining and processing of people's gold produces impacts on the surrounding environment. Some residents immediately dumped the waste gold processing results into the environment. It is necessary to analyze the actual condition of mercury pollution based on a map of the level of pollution vulnerability to determine the size of the level of difficulty and the ease of polluted substances to affect surface water quality. The purpose of this study is to analyze the actual condition of the level of vulnerability of surface water pollution around the study area. The method used in this study is a survey method and field mapping, sampling methods: purposive sampling, laboratory analysis methods, mathematical methods, and descriptive evaluation methods. Calculation of the level of vulnerability of surface water is the PCSM (Point Count System Model) method with 3 parameters, namely land use, slope, and rainfall. Overlay is done between the level of pollution vulnerability map with the actual conditions of pollution in the field. The results showed the study area has a level of vulnerability to surface water pollution in the study area including the classification of quite vulnerable and very vulnerable. Based on the results of the study it can be concluded that the total score of 36-43 included in the vulnerability class is quite vulnerable. The total score of 43 - 50 is included in the very vulnerable vulnerability class. Actual mercury levels in the study area were known in a row AP1-AP6 samples were 0,00046 mg / L; <0.00006 mg / L; <0.00006 mg / L; <0.00006 mg / L; 0,00039 mg / L and <0,00006 mg / L. These results indicate that surface water in the study area has not been contaminated with mercury because its value is brought to all quality standards.Â Â